An Overview on Azure Cloud Cognitive Services Oriented to Text, Face, Image, and Video - Pedro MARTINS; Cristina WANZELLER; Filipe SA; Maryam ABBASI (Communications of International Proceedings, 2020)
Features analysis such as, sentiment, colors, faces, objects are nowadays provided by web services which are dedicated to text analysis, images, video, and face recognition services. These services are a part of an overall Cloud-Vision process to determine the match-likelihood of each object/text/face to a template element from a database. Microsoft Azure is a growing suite of services in the cloud that provide among other services face recognition, video analytics, image analytics, text analytics to the general public, for instance: banking, public services, private companies, cellphone users. All of these potential users raise the interest in services that can be easily used and if necessary, to scale without a substantial initial investment. In this article are tested and compared four cognitive (Azure based) services, first oriented to text, second oriented to detect general purpose objects in images, third for face recognition applied to photos, and finally, the fourth service oriented to video. All the services are described, tested and compared, regarding, how to set up, pros and cons, points in common, and their learning curve.
Keywords: Azure; Visual computing; Text analysis; Face recognition; Video; Sentiment; Cloud service; Cognitive.